Elastic Waves in Generalized Thermo-Piezoelectric Transversely Isotropic Circular Bar Immersed in Fluid (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a mathematical model is developed to study the wave propagationin an infinite, homogeneous, transversely isotropic thermo-piezoelectric solidbar of circular cross-sections immersed in inviscid fluid. The present study is basedon the use of the three-dimensional theory of elasticity. Three displacement potentialfunctions are introduced to uncouple the equations of motion and the heat andelectric conductions. The frequency equations are obtained for longitudinal and flexuralmodes of vibration and are studied based on Lord-Shulman, Green-Lindsay andClassical theory theories of thermo elasticity. The frequency equations of the coupledsystem consisting of cylinder and fluid are developed under the assumption of perfect-slipboundary conditions at the fluid-solid interfaces, which are obtained for longitudinaland flexural modes of vibration and are studied numerically for PZT-4 materialbar immersed in fluid. The computed non-dimensional frequencies are comparedwith Lord-Shulman, Green-Lindsay and Classical theory theories of thermo elasticityfor longitudinal and flexural modes of vibrations. The dispersion curves are drawnfor longitudinal and flexural modes of vibrations. Moreover, the dispersion of specificloss and damping factors are also analyzed for longitudinal and flexural modes ofvibrations.